Phenolic Characteristics and Antioxidant Activity of Merlot and Cabernet Sauvignon Wines Increase with Vineyard Altitude in a High-altitude Region - Jin, Xiao-duo; Wu, Xuan; Liu, Xu (South African Journal of Enology and Viticulture, 2017)
Altitude, as an important factor in the expression of terroir, may affect wine quality. We evaluated the effect of altitude and its related climatic conditions on the phenolic characteristics and antioxidant activity of red wines made from grapes originating from high-altitude areas. The content of total phenolic compounds, total flavonoids and total anthocyanins increased with altitude in Merlot (ME) and Cabernet Sauvignon (CS) wines. Cabernet Sauvignon wines showed richer tannins with increasing altitude. Merlot and CS wines from higher altitude vineyards, showed a greater antioxidant capacity. Salicylic acid, syringic acid, caffeic acid, (+)-catechin, (−)-epicatechin, and the sum of individual phenolic compounds in the wines increased with altitude based on the results of HPLC. The scores of the sensory evaluation of ME wines increased with higher altitude. The highest score was determined for CS wine originating from 2 608 m. A clear grouping of wines according to grape cultivar and vineyard altitude was observed by principal component analysis. Regression analysis showed that altitude, followed by sunshine hours, made the greatest contribution to differences in the phenolic characteristics and antioxidant activity of red wines at different sites in a high-altitude region.